Estimation and Adjustment of Polarization Errors in Conical Scan Method - A. A. Bludov; G. A. Gorbatovskij; V. S. Pavlov; A. F. Suvorov (Известия высших учебных заведений России: Радиоэлектроника, 2018)
The article proposes a solution of a problem of polarization error compensation for radar object direction finding by means of conical scan method. The solution is considered at signal processing level that makes possible to avoid polarization limitations in antennas engineering. The purpose of the article is to substantiate a model for polarization-induced errors by conical scan direction finding method and to develop an algorithmic technique for the considered method correction with regard to arbitrary polarization conditions of radar interaction. The results are presented by analytical model along with quantitative estimates of polarization-induced errors of direction finding and the computational procedure of the error compensation as well as by analysis of imperfectness factors for the proposed procedure exposing its practical applicability.